Characterization of Chromium-tris(catecholate) Complex: A Theoretical Study - Matin, Mohammad A; Islam, Mazharul M; Aziz, Mohammed A (Dhaka University Journal of Science, 2017)
Phenolic compounds generally have special smell and are easily soluble in water, organic solvents (alcohols, esters, chloroform, ethyl acetate) and in alkali. Phenols produce coloured complexes with heavy metal ions, such as with chromium ion. The molecular details underlying the cross-linking mediated by transition metal ions are largely unknown. Using HF/DFT hybrid approach B3LYP, this study examines the structure, binding energy, spectroscopic and electronic properties of complex formed by the attachment of Cr3+ with a catechol ligand. Our study shows that the binding of Cr3+ with the catechol ligand is not as strong as the binding of other metal ions with catechol.The calculated FTIR spectra show strong IR intensities due to large charge polarization. The UV-Vis absorption spectrum of the tris-catecholato-Cr3+complex shows a clear ligand-to-metal charge transfer. The calculated electronic band gap is 4.06 eV which is in the range of transition metal ion tris-catechol complexes. Thermodynamic properties studied in this work show that the metal ion-ligand binding energy (532.99 kcal/mol) is close to those of the hexa-aqua complexes (ranging from 540 to 553 kcal/mol). Dhaka Univ. J. Sci. 65(2): 113-117, 2017 (July)